ANALISIS TINGKAT KECEMASAN SISWA KELAS TINGGI PADA PEMBELAJARAN MATEMATIKA DI SDN 3 CISERO - Fitriyah, Sefti; Oktaviani, Seli; Indriati Widyaningsih, Yennie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research is motivated by the phenomenon of student anxiety towards mathematics which can hinder the learning process and academic achievement. Mathematics is often perceived as a difficult and frightening subject, thereby causing psychological pressure that negatively impacts students’ motivation and self-confidence. Based on problem identification, students hold negative perceptions of mathematics learning and experience anxiety during classroom learning activities. The aim of this study is to analyze the anxiety level of upper-grade students in participating in mathematics learning at SDN 3 Cisero. To achieve this objective, this research employs a quantitative approach with a survey method. The population of this study consist of all upper-grade students at SDN 3 Cisero, with a sample of 16 students comprising 8 fourth-grade students and 8 fifth-grade students selected using saturated sampling technique. The data collection instrument was a mathematics anxiety questionnaire developed based on anxiety indicators covering aspects of nervousness, restlessness, displeasure, and difficulty concentrating. The questionnaire consisted of 35 valid statements after undergoing validity testing using Pearson Product Moment correlation with an rtable value of 0.497. Furthermore, the reliability test using Cronbach’s Alpha showed a value of 0.983, indicating that the instrument is highly reliable. Subsequently, the data were analyzed by categorizing anxiety levels into three categories: low, moderate, and high based on respondents’ total scores. The research result showed that out of 16 respondents, 11 students (69%) experienced mathematics anxiety in the high category, 5 students (31%) in the moderate category, and no dtudents in the low category. Thus, these findings indicate that the majority of upper-grade students at SDN 3 Cisero experience high levels of anxiety in mathematics learning.